Cultural Dynamics of Climate Change and the Environment in Northern America - Sommer, Bernd (Climate and Culture, 2015)
In Cultural Dynamics of Climate Change and the Environment in Northern America academics from various fields such as anthropology, art history, cultural studies, environmental science, history, political science, and sociology explore society-nature interactions in - culturally as well as ecologically - one of the most diverse regions of the world.; Readership: All interested in the cultural dimensions of climate change, and anyone concerned with environmental history, environmental sociology as well as environmental policy in North America.